Potential involvement of dietary advanced glycation end products in impairment of skeletal muscle growth and muscle contractile function in mice. Issue 1 (17th January 2017) - Egawa, Tatsuro; Tsuda, Satoshi; Goto, Ayumi; Ohno, Yoshitaka; Yokoyama, Shingo; Goto, Katsumasa; Hayashi, Tatsuya
Abstract: Diets enriched with advanced glycation end products (AGE) have recently been related to muscle dysfunction processes. However, it remains unclear whether long-term exposure to an AGE-enriched diet impacts physiological characteristics of skeletal muscles. Therefore, we explored the differences in skeletal muscle mass, contractile function and molecular responses between mice receiving a diet high in AGE (H-AGE) and low in AGE (L-AGE) for 16 weeks. There were no significant differences between L-AGE and H-AGE mice with regard to body weight, food intake or epididymal fat pad weight. However, extensor digitorum longus (EDL) and plantaris (PLA) muscle weights in H-AGE mice were lower compared with L-AGE mice. Higher levels of N ε -(carboxymethyl)-l -lysine, a marker for AGE, in EDL muscles of H-AGE mice were observed compared with L-AGE mice. H-AGE mice showed lower muscle strength and endurance in vivo and lower muscle force production of PLA muscle in vitro . mRNA expression levels of myogenic factors including myogenic factor 5 and myogenic differentiation in EDL muscle were lower in H-AGE mice compared with L-AGE mice. The phosphorylation status of 70-kDa ribosomal protein S6 kinase Thr 389, an indicator of protein synthesis signalling, was lower in EDL muscle of H-AGE mice than that of L-AGE mice. These findings suggest that long-term exposure to an AGE-enriched diet impairs skeletal muscle growth and muscle contractile function, and that these muscle dysfunctions may be attributed to the inhibition of myogenic potential and protein synthesis.